Academic Integrity in Canada: An Enduring and Essential Challenge - Christensen Hughes, Julia; Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2023)
In this session, Dr. Julia Christensen Hughes and Dr. Sarah Elaine Eaton will reflect on academic integrity in Canada, synthesize their various contributions, and challenge future practice. Drawing from their book, Academic Integrity in Canada: An Enduring and Essential challenge, they will highlight their experience and insights, since the seminal work of Christensen Hughes and McCabe (2006), focusing on the enduring and essential challenge of building cultures and practices aligned with academic integrity in Canadian higher education today. Participants will gain insight into current challenges and strategies for supporting academic integrity in their own administrative and teaching and research practice.